CONCEPTS OF PASSIVE AND ACTIVE VOCABULARY IN FOREIGN LANGUAGE TEACHING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This paper examines the role of lexical skill development in foreign language learning, with particular reference to English. Special attention is given to the process of semantization and the effectiveness of visual support and contextualization in facilitating vocabulary acquisition and retention. It also outlines the distinctions between active, passive, and external vocabulary, emphasizing the dynamic nature of lexical competence and the challenges learners encounter in expanding their usable vocabulary.